1954
DOI: 10.1063/1.1740412
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orbital Theory of Orientation in Aromatic, Heteroaromatic, and Other Conjugated Molecules

Abstract: provided comparisons are made only between closely related compounds. This observation suggests that the central atom is strongly involved in the transition concerned. Although the data presented here are insufficient to make a decision on this point, it is not unlikely that the end absorption corresponds to a dissociation process, as Milazzo has proposed. 7 EXPERIMENTAL All compounds were either obtained from commercial sources or prepared in this laboratory by known THE JOURNAL OF CHEMICAL PHYSICS methods. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
283
0
9

Year Published

1959
1959
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 707 publications
(295 citation statements)
references
References 12 publications
3
283
0
9
Order By: Relevance
“…6 The predicted position of electrophilic attack is, on the contrary, at the C-4 position and is in agreement with the experimentally observed products. 13 To the best of our knowledge, however, there are no literature reports concerning cycloaddition reactions of acridine where this acts as a 2π component.…”
Section: Methodsmentioning
confidence: 99%
“…6 The predicted position of electrophilic attack is, on the contrary, at the C-4 position and is in agreement with the experimentally observed products. 13 To the best of our knowledge, however, there are no literature reports concerning cycloaddition reactions of acridine where this acts as a 2π component.…”
Section: Methodsmentioning
confidence: 99%
“…Electrophiles tend to approach S roughly 20" from the perpendicular to the plane through atoms Y-S-Z, with values ranging from 0" to 40". In terms of the "frontier orbital" model (14,15), this direction corresponds to the highest occupied molecular orbital (HOMO), which is a sulfur lone-pair orbital. Nucleophiles, on the other hand, were shown to approach the sulfur atom approximately along the extension of one of the two covalent bonds to S , which was identified as the lowest unoccupied molecular orbital (LUMO), the antibonding orbital, a*.…”
Section: Methodsmentioning
confidence: 99%
“…I t is suggested that the radical is highly distorted by steric hindrance and the distribution of the unpaired electron is restricted to the naphthalene nucleus to which the peroxide oxygen atom is attached. By the simple LCAO-MO method, the density of the frontier electrons, i.e., the electrons in the highest occupied energy level, in P-substituted naphthalene was calculated by Fukui et al (4). Based on their result, the protons which contribute to the hyperfine splitting can be assigned to those attached to the starred carbon atoms in (111).…”
Section: Notesmentioning
confidence: 99%